2016
DOI: 10.1128/jb.00686-15
|View full text |Cite
|
Sign up to set email alerts
|

Yersinia Type III Secretion System Master Regulator LcrF

Abstract: c Many Gram-negative pathogens express a type III secretion (T3SS) system to enable growth and survival within a host. The three human-pathogenic Yersinia species, Y. pestis, Y. pseudotuberculosis, and Y. enterocolitica, encode the Ysc T3SS, whose expression is controlled by an AraC-like master regulator called LcrF. In this review, we discuss LcrF structure and function as well as the environmental cues and pathways known to regulate LcrF expression. Similarities and differences in binding motifs and modes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 81 publications
0
53
0
Order By: Relevance
“…LcrF expression is upregulated at 37˚C, mammalian host body temperature, and upon calcium depletion, which is thought to mimic contact with host cells [33,[35][36][37][38]. LcrF thermal control is mediated by host temperature dependent degradation of the negative regulator YmoA to activate lcrF transcription at mammalian body temperature and an RNA thermometer that represses LcrF translation at environmental temperatures [32,35,38,39]. A recent study showed that low calcium or host cell contact lead to secretion of a T3SS cargo protein and regulator, YopD, that ultimately affects lcrF mRNA stability [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LcrF expression is upregulated at 37˚C, mammalian host body temperature, and upon calcium depletion, which is thought to mimic contact with host cells [33,[35][36][37][38]. LcrF thermal control is mediated by host temperature dependent degradation of the negative regulator YmoA to activate lcrF transcription at mammalian body temperature and an RNA thermometer that represses LcrF translation at environmental temperatures [32,35,38,39]. A recent study showed that low calcium or host cell contact lead to secretion of a T3SS cargo protein and regulator, YopD, that ultimately affects lcrF mRNA stability [40].…”
Section: Discussionmentioning
confidence: 99%
“…The region containing the IscR binding site upstream of lcrF is 100% identical between Y. pseudotuberculosis and Y. pestis [32]. Therefore, we sought to determine if T3SS activity in Y. pestis also required IscR despite the difference in life cycles carried out by enteropathogenic Yersinia compared to Y. pestis.…”
Section: Iscr Is Required For Type III Secretion In Yersinia Pestismentioning
confidence: 99%
“…Our finding that the 5′ UTR of psaE regulates translation initiation of psaE in response to a temperature upshift resembles the recently described mechanism regulating temperature-dependent synthesis of LcrF, a major virulence regulator of the type III secretion system (T3SS) in Yersinia spp. ( 37 , 41 ). Similar to our findings with PsaE/PsaF, the synthesis of LcrF in Y. pestis is significantly increased at high temperature and corresponds with the expression of type III secretion system (T3SS) genes regulated by LcrF ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite differences in pathogenesis, these virulent Yersinia species have several common virulence factors, including the 70-kb virulence plasmid (pCD1 in Y. pestis and pYV in enteropathogenic Yersinia ) and the yersiniabactin (Ybt) system (Brubaker, 1991 ; Heesemann et al, 1993 ; Cornelis et al, 1998 ). The 70-kb plasmid contains dozens of genes encoding structural components of a type III secretion system (T3SS), and also encodes several T3SS effector proteins called Yersinia outer proteins (Yops) and their dedicated chaperones to subvert the innate immune system of the hosts (Bliska et al, 2013 ; Schwiesow et al, 2015 ). Since enzymes/toxins/effectors delivered by secretion systems play a crucial role in the interaction between pathogens and their hosts or competitors, the various types of secretion systems attract interest in the research on pathogenic bacteria.…”
Section: Introductionmentioning
confidence: 99%